Prediksi masa simpan kerupuk ikan Palembang melalui pendekatan angka total oksidasi (totox) dengan metode Accelerated Self-life Test (ASLT) [Prediction of the shelf-life of Palembang fish crackers through the total oxidation number (totox) approach with the Accelerated Self-Life Test (ASLT) method] - Aldila Din Pangawikan; Retno Cahya Mukti; Dwi Inda Sari; Sherly Ridhowati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Fish crackers have a short shelf life due to rancidity produced by oxidation damage. This study aims to determine the shelf life of fish crackers using the total oxidation number (Totox) approach. The shelf life test was carried out using the accelerated shelf-life test (ASLT) technique following the Arrhenius model. The experiment was carried out using stratified storage temperatures ranging from 25 °C, 35 °C, and 45 °C for 15 days to follow the level of oxidation damage through Totox numbers. The results of this study indicate that the ASLT technique can be used to predict the shelf life of fish crackers whose core damage is due to oxidation reactions. The prediction of the shelf life based on the Totox number is 118 days; for that, it is recommended to consume Palembang fish crackers below that time.